Patient‐Reported Factors Influencing Clinical Trial Participation: An In‐depth Analysis of Patients With Lupus and Rheumatoid Arthritis - Aliza Bloostein; Roberto Caricchio (ACR Open Rheumatology)
Systemic lupus erythematosus (SLE), a chronic systemic autoimmune disease, has only three approved therapies, despite a rapidly expanding number of clinical trials. Trials in SLE struggle to recruit patients and fail to fully enroll. Rheumatoid arthritis (RA), another chronic autoimmune disease, has had more success in clinical trial enrollment. This article's goal is to analyze literature to compare patient perspectives on factors determining clinical trial participation in SLE and RA populations. A literature review regarding patient attitudes, perceptions, perspectives about, and barriers toward clinical trials was conducted. RA literature used more quantitative methods, whereas SLE literature used more qualitative methods. Literature revealed that patients with SLE and patients with RA reported similar factors motivating trial participation, such as altruism, personal benefit, and trust in physician, but patients with SLE were uniquely motivated by strong social networks. In terms of disadvantages to trial participation, patients with SLE and RA similarly reported fear of unknown interventions, complications, and side effects; only in the population of patients with SLE were fears of a disease flare and of not qualifying reported. SLE literature had a specific emphasis on factors influencing Black patient participation. This review informs steps for future research to better evaluate perceptions of clinical trials in patients with SLE and provides a framework for methods to increase SLE trial participation, including recognizing fear of changing treatment regimen as an explanation for the paucity of SLE trial participation, incorporating clinical trials as usual care for patients with SLE, and using less stringent inclusion and exclusion criteria for trials.